A Correlational Study on the Stress Level and Academic Performance of Nursing Students (Journal of Basic and Applied Research in Biomedicine, 2022)
This study assesses the level of stress and its relationship to the academic performance of the respondents. This study used descriptive-correlational design, and total enumeration was utilized, with 34 respondents. A questionnaire was the primary instrument of this study. Statistical used in this study was frequency, percentage, mean, and Pearson-r. Results include: most (76.50%) of the respondents are relatively young, most (82.30%) of the respondents are females, some (38.20%) of the respondents are fourth-year. A vast majority (64.70%) of the respondents’ primary source of stress is academic works. The mean score of the stress is 20.59. The respondents academic works have mean score of 2.25, and Pearson-r score is (r= 0.71, n=34, p=0.00). The researchers conclude that the nursing program in one of the universities in Dagupan City has relatively young students that are female dominated in their senior year. The respondents have a moderate level of stress, and the primary source of their academic works is the primary source of their stress. The respondents are satisfactorily performing in their academics. Also, it was found out that as the respondents’ stress level raises their academic performance declines.